Key Events and Their Effect on Mobility Biographies: The Case of Childbirth - Lanzendorf, Martin (International journal of sustainable transportation, 2010)
Over the last few years, travel-behavior researchers have generally acknowledged the importance of habits and key events in understanding travel-behavior changes. The purpose of this study is to contribute to the evolving research field of mobility biographies. With a retrospective, qualitative survey, 20 parents of small children are questioned about key events affecting their travel behavior and in particular the role of childbirth in this respect. The findings reveal that the commonly expected car-dependency after childbirth is only one pattern among others such as the stability or even increase of green mode use.